Beyond Boyer: SoTL in the Context of Interesting Scholarly Things - Bruce B. Henderson (Park University, 2009)
The positive effects of Ernest Boyer's broader definition of scholarship have been attenuated by stress on published outcomes as indicators of all his scholarships, including the scholarship of teaching and learning (SoTL). At universities outside the research university sector, we need to find ways to recognize and reward a wide variety of interesting scholarly things related to teaching that are not likely to meet the formal assessment criteria that have come to define the SoTL category of scholarship. The faculty's scholarliness in teaching should be recognized and evaluated directly.